One-Step Repair in Talar Osteochondral Lesions: 4-Year Clinical Results and T2-Mapping Capability in Outcome Prediction. (March 2013) - Giannini, Sandro; Buda, Roberto; Battaglia, Milva; Cavallo, Marco; Ruffilli, Alberto; Ramponi, Laura; Pagliazzi, Gherardo; Vannini, Francesca
Background: A recent one-step arthroscopic technique based on bone marrow–derived cell transplantation has achieved good results in repairing osteochondral lesions of the talus (OLTs), overcoming some of the drawbacks of older techniques. Purpose: To report the results after 4 years of a series of patients who underwent a one-step repair of osteochondral lesions of the talar dome, as well as the capability of magnetic resonance imaging (MRI) using a T2-mapping sequence to predict the clinical outcome. Study Design: Case series; Level of evidence, 4. Methods: Forty-nine patients (age [mean ± SD], 28.08 ± 9.51 y) underwent a one-step repair of OLTs. Patients were evaluated clinically by American Orthopaedic Foot and Ankle Society (AOFAS) scores and radiographs and underwent MRI preoperatively and during postoperative follow-ups at predetermined times. In all patients, the cells were harvested from the iliac crest, concentrated, and loaded on a scaffold that was implanted arthroscopically. Results: The overall AOFAS score (mean ± SD) improved from 63.73 ± 14.13 preoperatively to 82.19 ± 17.04 at 48 ± 6.1 months ( P < .0005), with best results at the 24-month follow-up. A significant decrease in the clinical score was observed between 24 and 36 months postoperatively ( P = .001) and between 24 and 48 months ( P < .005). The T2-mapping analysis showed regenerated tissue with T2 values of 35 to 45 milliseconds, similar to hyaline cartilage, in a mean of 78% ± 16% of the repaired lesion area. The time between the occurrence of trauma and surgery was found to negatively affect the clinical outcome at the latest follow-up; patient's age and lesion size influenced the early clinical results but did not affect the outcome at final follow-up. The stability of clinical results over time and the percentage of tissue with values similar to hyaline cartilage evidenced by MRI T2 mapping showed a tendency to correlate at the last follow-up ( r = 0.497, P = .06). Conclusion: One-step repair of OLTs had good clinical results that were durable over time, even though there was a slight decrease in AOFAS score at the latest follow-up. The quality of the regenerated tissue detected by MRI T2 mapping directly correlated with the clinical results.